PEMBENTUKAN KARAKTER MELALUI PENDIDIKAN SOSIOLOGI - Kamil P, Gurniwan (Fakultas Ilmu Sosial Universitas Negeri Padang, 2015)
The purpose of this article is to explain the essence of student’s character formation through educational and family institutions. It is also discuss the central rule of moral education in both institutions. Furthermore it explains the three pillars of education such as school, family and society. These three pillars have significant educational function. In the last section of this article, the writer trays to raise the case of character education through the subject of sociology for the senior middle school (SMA) students. It is believed that sociology contains mach examples and reading materials for character education. Keywords: Character, character education, sociology education